An analysis of the close relationships between stress and depression from the psychoneuroendocrinological perspective - Pablo Martino (CAEN, 2014)
This paper is a theoretical review whose general objective was to analyze the complex links between two frequently recurring phenomena in the field of mental health: the stress and depression, from the psychoneuroendocrinological point of view, considering the implication of the cortisol hormone on the relationship mentioned above. For this purpose we proceeded through a database search in Medline, Pubmed, Wiley Online Library, and Scielo data. It was concluded that chronic stress and some forms of depression would establish a continuum. They have neurobiological and pathophysiological basis with many similarities. In addition, a hostile environment during early childhood would increase the vulnerability to the stress and to suffering from depression in the adulthood. The epigenetic studies indicated the methylation of glucocorticoid receptor gene as mechanism associated with the development of this vulnerability. Finally, so much the psychotherapy cognitive behavioral as the administration of antidepressing medication, they have demonstrated to reach his therapeutic effects across the increase in neural plasticity on cerebral key structures in the neurobiological processes involved in the stress.